POLY MVA – a dietary supplement containing α-lipoic acid palladium complex, enhances cellular DNA repair. (13th June 2011) - Menon, Aditya; Nair, Cherupally Krishnan Krishnan
POLY MVA, a commercially available health supplement containing α-lipoic acid palladium complex, was evaluated for its potential to enhance the repair of radiation-induced DNA damage. Treatment of human peripheral blood leukocytes with POLY MVA immediately after radiation exposure enhanced the repair of cellular DNA as revealed by comet assay. Post-irradiation administration of POLY MVA to mice resulted in faster cellular DNA repair, as revealed from the increased Cellular Repair Index (CRI) of blood leukocytes and bone marrow cells. Exposure of mice to 2 Gy whole-body gamma radiation resulted in the formation of strand breaks of cellular DNA of bone marrow cells, and the unrepaired strand breaks eventually lead to the formation of micronuclei in the reticulocytes. Administration of POLY MVA under post-irradiation conditions showed a decrease in the number of micronucleated reticulocytes. Thus, the studies under ex vivo and in vivo conditions revealed that the enhancement of DNA repair could be one of the mechanisms underlying radioprotection by POLY MVA.